Nepal : Staff Report for the 2012 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2012)
Nepal is a post-conflict state seeking to formalize democracy in a challenging environment. Significant headway toward a new state has been made since the 2006 peace accord. Progress on a range of technical issues (including public financial management, monetary policy, and financial sector supervision) has also been achieved. However, the failure of the constituent assembly to meet an end-May 2012 deadline to ratify a new constitution is a serious setback, and a major impediment to macroeconomic management and prospects for growth. The subsequent dismissal of the constituent assembly in June 2012 has left day-to-day operations in the hands of a caretaker government. New elections are notionally slated for April 2013, but will require fractured political parties to agree on an interim consensus government. In the meantime, key articles of legislation (such as the government budget) have been delayed. More broadly, the lack of a consensus government and functioning parliament appear to be dampening investment (foreign and domestic), keeping potential donor support at bay, and undermining prospects for sensitive financial sector and state enterprise reforms.